Association between medication adherence and blood pressure control and factors associated with antihypertensive medication adherence in the Melaka Tengah District: A cross-sectional survey - Siti Zaleha Suleiman; Mila Nu Nu Htay; Htoo Htoo Kyaw Soe; Cherlynn Low Li Ying; Siti Hawa Alias; Syamimi Yussof; Keng Wei Xiong; Chong Karleen; Mohammad Faiz Sahiran; Muhamad Hafiz Harun; Azman Othman; Rosmiza Abdullah; et al. (Malaysian Family Physician)
Introduction: The burden of cardiovascular disease and early morbidity and mortality is exacerbated by hypertension. According to the 2019 National Health and Morbidity Survey, 30% of adults in Malaysia aged over 18 years had hypertension. Our study aimed to investigate the association between medication adherence and blood pressure control and the factors associated with antihypertensive medication adherence. Methods: This cross-sectional study was conducted among adult patients with hypertension who had been under treatment at public primary health clinics in the Melaka Tengah District. A self-administered questionnaire was used, and blood pressure was measured. Descriptive and multivariate logistic regression analyses were conducted using the Statistical Package for the Social Sciences (version 28). Results: A total of 1531 patients were recruited in this study. Among them, 74.1% had good antihypertensive medication adherence, and 51.4% had their blood pressure controlled. Medication adherence was significantly associated with blood pressure control (P<0.005). The multivariate analysis showed that the determinants for antihypertensive medication non-adherence were Malay ethnicity, secondary education, farther distance from the clinic, experience of side effects of antihypertensive medications, concern about long-term side effects and usage of alternative medicine (P<0.05). Taking multiple antihypertensive medications was the only factor associated with uncontrolled blood pressure (P<0.05). Conclusion: Addressing issues on medication adherence is important to ensure blood pressure control. The factors associated with non-adherence should be closely monitored to improve blood pressure control and prevent adverse health outcomes. Single-pill combination antihypertensive medications are encouraged to reduce pill burden and improve blood pressure control.